Pengaruh Kompensasi Langsung dan Kompensasi Tidak Langsung terhadap Semangat Kerja Karyawan di PT. Bandar Abadi Batam - Shinta Wahyu Hati; Serlina Simangunsong (Politeknik Negeri Batam, 2016)
This research to find out the purpose of known direct compensation and indirect compensation to spirited employee at PT.Bandar Abadi of known variable most dominant effected on Spirit Company. The sampling technique used the method of jenuh sampling with 40 respondents. The Interviews and questionnaires are used in data collection methods. This research method using multiple linear regression. The result showed that the direct compensation and indirect compensation effect of simultan and partial to sprited employee at PT.Bandar Abadi. While the variables that have dominant effect on spirit at PT.Bandar Abadi is direct compesation with salary indicator and intensif. The related of teori research direct compensation will be variabel have effect it’s the most dominant can suggestion to company of pay attention direct compensation to advance giving spirit for promotion of company so that prevour on working can be improved.